2011
DOI: 10.1002/ps.2260
|View full text |Cite
|
Sign up to set email alerts
|

Developmental studies of transgenic maize expressing Cry1Ab on the African stem borer, Busseola fusca; effects on midgut cellular structure

Abstract: This study confirms the potential for Bt maize, when used as part of an IPM programme, for control of B. fusca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Bt corn (MON810) significantly reduced survival, developmental rate and pupal and adult weight of Busseola fusca compared with parental line. These differences were more pronounced with 2 nd instar larvae than with 3 rd instar larvae 41 . Valadez-lira et al .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Bt corn (MON810) significantly reduced survival, developmental rate and pupal and adult weight of Busseola fusca compared with parental line. These differences were more pronounced with 2 nd instar larvae than with 3 rd instar larvae 41 . Valadez-lira et al .…”
Section: Discussionmentioning
confidence: 82%
“…Some reports have indicated that larger lepidopteran larvae are more Bt tolerant than smaller larvae 12 39 40 41 . Bt corn (MON810) significantly reduced survival, developmental rate and pupal and adult weight of Busseola fusca compared with parental line.…”
Section: Discussionmentioning
confidence: 99%
“…- George et al (2012) conducted laboratory bioassays to investigate the impact in terms of survival and development of diets containing maize MON 810 leaves on ASB, which is a target lepidopteran maize pest in South Africa. Weight, development time and mortality of larvae exposed to diets containing either Bt-maize or non-Bt-maize were measured.…”
Section: Results From the Literature Searchmentioning
confidence: 99%